The effect of social support to postpartum depression in postpartum mother in 2018 - Dessy Hertati; Evi Nurhidayati (Universitas 'Aisyiyah Yogyakarta, 2019)
The Effect Of Social Support To Postpartum Depression in Postpartum Mother. Post-partum mother have the potential of depression. Their new role as mother gives a higher burden on their mental health. According to the American of Pedriatrics, a retrospective study conducted by nursing found that one of seven women was hospitalized for depression during pregnancies up to one year after childbirth. The prevalence of maternal depression in 2 weeks after delivery was 80-85% and more than 8-15% will develop into postpartum depression. Pregnant mother who did not receive social support were associated with the incidence of postpartum depression with an OR of 2.12 to 3.38 as well as postpartum mothers who received less social support associated with postpartum depression with OR values of 2.06 to 9.64.The study was conducted by literature studies on 10 previous studies about social support variables and the occurrence of postpartum depression. It was found that social support is essential for post-partum mothers in order to keep their confidence to take care their babies and adapt to new things. The social supports were expected from husbands, families, health professionals and environment. Several factors such as culture, education level, demography, and birth experience have the effects on the potential of post-partum depression. Low level of social support increased maternal depression and reduce maternal mental health within four weeks after delivery. High levels of depression can lead to self-harming, acute depression symptoms such as sadness, crying, irritability, anxiety, concentration difficulty, lability of feelings and sleep and appetite disorders, even at an advanced level, it can lead to suicide. In order to minimize and overcome postpartum depression, midwives are expected to provide promotive preventive care on mental health both in prenatal and antenatal periods.